Coadministration of Anti-Viral Monoclonal Antibodies With Routine Pediatric Vaccines and Implications for Nirsevimab Use: A White Paper - Esposito, Susanna; Abu-Raya, Bahaa; Bonanni, Paolo; Cahn-Sellem, Fabianne; Flanagan, Katie L.; Martinon Torres, Federico; Mejias, Asuncion; Nadel, Simon; Safadi, Marco A. P.; Simon, Arne (Frontiers in Immunology, 2021)
Routine childhood vaccinations are key for the protection of children from a variety of serious and potentially fatal diseases. Current pediatric vaccine schedules mainly cover active vaccines. Active vaccination in infants is a highly effective approach against several infectious diseases; however, thus far, for some important viral pathogens, including respiratory syncytial virus (RSV), vaccine development and licence by healthcare authorities have not been accomplished. Nirsevimab is a human-derived, highly potent monoclonal antibody (mAb) with an extended half-life for RSV prophylaxis in all infants. In this manuscript, we consider the potential implications for the introduction of an anti-viral mAb, such as nirsevimab, into the routine pediatric vaccine schedule, as well as considerations for coadministration. Specifically, we present evidence on the general mechanism of action of anti-viral mAbs and experience with palivizumab, the only approved mAb for the prevention of RSV infection in preterm infants, infants with chronic lung disease of prematurity and certain infants with hemodynamically significant heart disease. Palivizumab has been used for over two decades in infants who also receive routine vaccinations without any alerts concerning the safety and efficacy of coadministration. Immunization guidelines (Advisory Committee on Immunization Practices, Joint Committee on Vaccination and Immunization, National Advisory Committee on Immunization, Centers for Disease Control and Prevention, American Academy of Pediatrics, The Association of the Scientific Medical Societies in Germany) support coadministration of palivizumab with routine pediatric vaccines, noting that immunobiologics, such as palivizumab, do not interfere with the immune response to licensed live or inactivated active vaccines. Based on the mechanism of action of the new generation of anti-viral mAbs, such as nirsevimab, which is highly specific targeting viral antigenic sites, it is unlikely that it could interfere with the immune response to other vaccines. Taken together, we anticipate that nirsevimab could be concomitantly administered to infants with routine pediatric vaccines during the same clinic visit.